Repetitive negative thinking mediates the relationship between addictive Facebook use and suicide-related outcomes: A longitudinal study - Brailovskaia, Julia (Curr Psychol, 2021)
Repetitive negative thinking (RNT) and addictive Facebook use have been shown to be associated with suicide ideation and suicidal behavior. The present longitudinal study aimed to investigate whether the association between addictive Facebook use and suicide-related outcomes is mediated by RNT. Data of 191 German Facebook users (M(age) = 26.17, SD(age) = 6.63) were assessed at two measurement time points over a one-year period (first measurement = T1, second measurement = T2) via online surveys. The significant positive association between addictive Facebook use (T1) and suicide-related outcomes (T2) was significantly mediated by RNT (T1). In contrast, a check test that included RNT (T1) as predictor and addictive Facebook use (T1) as mediator revealed no significant mediation effect. The current results demonstrate that if addictive Facebook use leads to RNT suicide ideation and attempts become likely. Therefore, RNT and addictive Facebook use should be taken into account when assessing individuals for risk of suicide.